2022
DOI: 10.3847/1538-4357/ac36d2
|View full text |Cite
|
Sign up to set email alerts
|

The VLA/ALMA Nascent Disk And Multiplicity (VANDAM) Survey of Orion Protostars. V. A Characterization of Protostellar Multiplicity

Abstract: We characterize protostellar multiplicity in 20 Current address: Niels Bohr Institute, University of Copenhagen, Øster Voldgade 5–7, DK-1350, Copenhagen K, Denmark. the Orion molecular clouds using Atacama Large Millimeter/submillimeter Array 0.87 mm and Very Large Array 9 mm continuum surveys toward 328 protostars. These observations are sensitive to projected spatial separations as small as ∼20 au, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 108 publications
6
37
0
Order By: Relevance
“…Ωτ cool decreases in radius, and the disks are commonly prone to fragmentation beyond 20-50 au. This is broadly consistent with the observation of a bimodal distribution of companion separation in protostellar systems (Tobin et al 2016(Tobin et al , 2022 where the peak at smaller separation (∼100 au) could be due to fragmentation. Note that such observation does not provide a very good constraint on whether fragmentation commonly occurs as the visibility and survival rate of fragments are still not well understood.…”
Section: Fragmentationsupporting
confidence: 91%
“…Ωτ cool decreases in radius, and the disks are commonly prone to fragmentation beyond 20-50 au. This is broadly consistent with the observation of a bimodal distribution of companion separation in protostellar systems (Tobin et al 2016(Tobin et al , 2022 where the peak at smaller separation (∼100 au) could be due to fragmentation. Note that such observation does not provide a very good constraint on whether fragmentation commonly occurs as the visibility and survival rate of fragments are still not well understood.…”
Section: Fragmentationsupporting
confidence: 91%
“…In a multiplicity study of all known protostars (94) in the Perseus molecular cloud, found a bimodal distribution of separation among binary/multiple systems, with peaks at ∼75 au and ∼3000 au. The bi-modal distribution was recently confirmed by a more detailed analysis of protostar separations in the Orion and Perseus molecular clouds (Tobin et al 2022). Based on these results, Tobin et al (2022) suggest that multiples with small separations (<500 au) are likely produced by both disk fragmentation and turbulent fragmentation with migration, and those with wide separation (> 10 3 au) result primarily from turbulent fragmentation.…”
Section: Introductionmentioning
confidence: 79%
“…The bi-modal distribution was recently confirmed by a more detailed analysis of protostar separations in the Orion and Perseus molecular clouds (Tobin et al 2022). Based on these results, Tobin et al (2022) suggest that multiples with small separations (<500 au) are likely produced by both disk fragmentation and turbulent fragmentation with migration, and those with wide separation (> 10 3 au) result primarily from turbulent fragmentation. Lee et al (2017) found a low-mass binary system in the earliest stages of formation with the rotation axes of their disks misaligned, suggesting that this binary system is likely formed due to turbulent fragmentation.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations